Evaluación financiera a la Empresa IMPEXSUREÑA “Cia.Ltda” de la Provincia de El Oro, del Cantón Huaquillas, periodo 2014 – 2015 - Delgado Espinoza, César Yampier (2017)
The Thesis "Financial Evaluation of the Company Impexsureña" Cia.Ltda "of the Province of El Oro, Huaquillas canton period 2014 - 2015" was elaborated with the general objective of carrying out a financial evaluation to the company and to report on the economic- Which will serve as a basis for making future decisions, that guide the proper administrative operation of the same and was developed based on both general and specific objectives. The development of the thesis work started with the collection of information that allowed to know the state in which the company is and an acknowledgment to define the application of the financial evaluation. Start with the financial and economic structure of the company through the vertical analysis with the purpose of knowing the participation and variation of the different items that intervened and is elaborated by determining the relative participation of each item on a common category that groups them, Made the horizontal analysis to establish the trends or variations of the different items in the balance sheet and the income statement. The financial indicators were also applied, which were represented graphically and interpreted, these were developed according to the need and operative activity that the company performed the basis was taken from the financial statements, applying the indicators of liquidity, 5 profitability, activity and Within this objective also applied the financial evaluation measures such as the calculation of EVA that measures the creation of value of the company through the net profit after tax in relation to the opportunity cost of shareholders , As well as the DuPont system that allows to verify if the profitability of the company is based on a wide margin of profit in sales, or is based on a high turnover of its assets and the Point of Balance that according to the requirements is based Based on sales, which allows determining the values of the income that the company needs so that it operates without losses or gains against costs. Finally, the financial evaluation report is presented to IMPEXSUREÑA "CIA.LTDA" to communicate about the conditions and financial position of the company and that serves as a tool for the timely decision of the executives, therefore to conclude said report The respective conclusions of the results and recommendations of the deficiencies are established, which will allow to improve the development and to determine good managerial strategies in progress of the same and oriented to the importance and the benefit of to elaborate periodically a financial evaluation